The necessary attitudes toward becoming a music teacher: a case study of music education students at the faculty of music, UiTM, Shah Alam / Muhammad Amin Sobri - Sobri, Muhammad Amin (2014)
Background of the topic This section is about the introduction of the study which includes background of the study, background of the Music Education department, problem statement, research objectives, research questions, significance of study, and definition of terms. Background of the study According to Mior (2011), the education system, through the school system, is a very important element for a country especially towards developing the society economically, politically and socially. The school system is not merely to educate the society, but it works as a channel to spread to the people concerning the national struggle that really emphasizes on the ethical values in the multiracial society for the sake of unity. Malaysia is a country that has multiple races, religions and cultures where it is best known for its plural society. The execution of the educational system must follow the needs and suitability of the people in Malaysia. Besides that, Malaysia is a developing country that is on the rise of modern development. Multiple means and actions had been planned and executed to achieve the national mission and vision. The execution has started even before this country had achieved its independence. Based on Syahmi (2012), Government's steps and efforts include various matters from all angles like the health aspect, education, transportation and many more. It is visible especially when Rahman Talib Report, Education Ordinance, Razak Report and many more had been created toward the development in the field of education. Nowadays, the field of education has definitely been lifted to a higher level when being a teacher is considered a career and a certified profession.